Effect of Titanium Dioxide Particle Size in Water-based Micro/Nanofluid as Quench Medium in Heat Treatment Process. (August 2019) - Prayogo, I.F; Muhammad, F.; Rakhman, D.; Putra, W.N.; Harjanto, S.
Abstract: Recently, nanofluid is used to improve the thermal conductivity of the quench medium in the heat treatment industry. In this research, ball-milled micro-sized TiO2 powder and nano-sized TiO2 particle were used and compared for their cooling characteristic in a micro/nanofluid. The micro/nanofluids were produced by mixing 0.1%, 0.3%, and 0.5% volume of both micro- and nano-sized particle into 100 ml of distilled water. The planetary ball mill was used at 500 rpm for 15 hours to reduce the dimension of micron-sized TiO2 . Composition characterization by Energy Dispersive Spectroscopy (EDS) showed that the powder used were free from impurities. Nanofluids were then used to quench S45C carbon steel samples, which heated at 1000°C for 1 hour. The hardness test result showed that the sample quenched with 0.5%addition of the nano-sized particle in nanofluid had the highest number up to 691 HV, almost 100HV increment from a water-quenched sample where the hardness was 598 HV, showing that the cooling rate in the nanofluid was much higher. The addition of micro-size particle in fluid generally had a lower cooling rate than the addition of nano-size particle.